Health and labour income of wage earners and self-employed workers in Cameroon - Benjamin Fomba Kamga; Arline Kengne Kamga; Martine Audibert (Institute for the Study of Labor (IZA), 2013)
The objective of this paper is to assess the relationship between the health and the income from work of wage earners and self-employed workers in Cameroon. Health status is measured by a self-assessment of an individual's health; and income is measured by the monthly wage of the wage earners and monthly profits of the self-employed workers. This paper uses a simultaneous equation model to explore the relationship between health and income, allowing for the endogeneity of health, income, and selection into each employment status. The data used in this study is obtained from the 2007 Cameroon household consumption survey. Using OLS estimates, we find a positive and significant effect of health on labour incomes for self-employed workers. Using TSLS IV estimates, we find that health has a positive and significant effect on incomes for self-employed women, but not for men. We also undertake a reverse effect analysis from income to health, using the ordered probit estimation process. We find that, for men, the effect of income on health status is positive and significant for wage earners. For women, this effect is positive and significant for the self-employed.
Keywords: I12; J21; J31; 330; health; labour income; wage earners; self-employed; Cameroon